Hypoxic – Ishemic Spinal Cord Lesions in Cerebral Palsy: A Case Report - Vadim, Belenky; Elena, Kozireva; Nadezhda, Plakhotina; Alexander, Skoromets; Pavel, Dugaev; Oleg, Leontiev (Current Practice in Medical Science Vol. 11, 2022)
Objective: To challenge the dominant conception of cerebral palsy as pathology restricted by the brain, by testing alternative hypothesis, that perinatal hypoxia – ischemia affects brain circulation just to the same extent, as it affects spinal circulation. Presentation of Case: We present the case of a 4-year-old male with lower paraplegia and delayed speech. Clinical examination revealed that the muscle tonus in the gastrocnemius and thigh adductors was increased bilaterally. The iliopsoas' muscle tonus was reduced bilaterally. Electrophysiological testing revealed evidence of decreased excitability of motoneurons at the L 2 - S 2 level. In addition to brain lesions, MRI has revealed spinal cord lesions at that level. A tortuous anterior spinal artery was discovered using MRI spinal angiography. The patient benefited from theophyllinum electrophoresis on the lower thoracic and first lumbar vertebrae, which improved his leg motor function. Discussion and Conclusion: Dr. Little, the first explorer of cerebral palsy, based his theory on a thorough postmortem examination performed by himself and his colleagues. According to the data obtained from the section, he reported the cerebral palsy to be caused by perinatal injury to either the brain or the spinal cord. However, the next explorer of this disorder, Dr. Freud, limited his pathlogoanatomic research to brain cuts only, diverting neurologists' attention away from the spinal cord. Nonetheless, our presentation demonstrates the involvement of the spinal cord in the pathogenesis of Cerebral Palsy, as well as the benefits of spinal therapy, and thus confirms Little's point of view.